Analisis Jaringan Rantai Pasok Sayuran Pakcoy Hidroponik untuk Peningkatan Pendapatan: Studi Kasus PT. Pagi Berkah Berjamaah, Bogor, Indonesia - Adessa Putri Rashesa; Irvanly D Sihombing; Nurahma Fauziah; Salsa Nur Maulida; Tania Amable Padang (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Pagi Farm is a Bogor regional company unit that cultivates various vegetables, one of which is bok choy vegetables for the bok choy vegetable needs of the community and as a stakeholder in the downstream supply chain activities for pak choy vegetables. This research aims to analyze the supply chain network for hydroponic bok choy vegetables to increase income. The research data used comes from primary data from conducting interviews with PT. Morning Congregational Blessing. R/C analysis to determine the feasibility of PT's Pakcoy Hydroponics vegetable business. Morning Congregational Blessing. The results of the research can be concluded that the bok choy supply chain at PT Pagi Berkah Berjamaah (Pagi Farm) is through PT Pagi Berkah Berjamaah (Pagi Farm) then to collectors then distributed to supermarkets and then to consumers. Based on the R/C analysis, the R/C results were > 1,68, which means that pak choy farming is feasible and profitable.